If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 8) = (9x + -4) Reorder the terms: (8 + 3x) = (9x + -4) Remove parenthesis around (8 + 3x) 8 + 3x = (9x + -4) Reorder the terms: 8 + 3x = (-4 + 9x) Remove parenthesis around (-4 + 9x) 8 + 3x = -4 + 9x Solving 8 + 3x = -4 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 8 + 3x + -9x = -4 + 9x + -9x Combine like terms: 3x + -9x = -6x 8 + -6x = -4 + 9x + -9x Combine like terms: 9x + -9x = 0 8 + -6x = -4 + 0 8 + -6x = -4 Add '-8' to each side of the equation. 8 + -8 + -6x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = -4 + -8 -6x = -4 + -8 Combine like terms: -4 + -8 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 6x+105=14x-7 | | 119-4x=41x+19 | | 8y+1000/Y=0 | | 2y^2-50y+308=0 | | 135+x=90 | | 8y+1000/Y | | 135+x=180 | | 4/5-2/4 | | -45=-6f(-3f-4) | | -2x+5y+7=0 | | x+40+5x+14+90=180 | | 6/7-2/5 | | 7x+2=13x-3 | | y^2+25y+154=0 | | 4/6-2/9 | | (x-4)(x-4)-25=0 | | 3*2-(2-5)=9 | | 8.3-0.6x=11.3 | | 5x+130=13x-6 | | 11.3-0.6x=11.3 | | 6X+5-8X+15= | | 7x^2-49x+17=0 | | 100-5x=31x+24 | | me=co*ol | | me=sexy | | 5x+2=-2+16 | | 12x^2-9x-10=0 | | 4x-y=3b | | x=dx | | -3/2-(24+6x)=9 | | 5=5unsghcm | | (n-15)(n+6)=n-15 |